Degrees of schematicity of verbal-noun constructions with the verb deixar in Brazilian Portuguese - Francisco de Souza, Edson Rosa [UNESP]; Prezotto Junior, Jose Roberto [UNESP] (Federal Univ Ceara, 2017)
The aim of the paper is to investigate, based on the theoretical premises of Traugott and Trousdale's (2013) constructional approach and Bybee's (2010) cognitive-functional approach, the verbal-noun (VN) constructions with the verb deixar in Brazilian Portuguese, which result from the association of a verb semantically light with a noun phrase. The hypothesis defended here is that the VN constructions with this verb show different degrees of schematicity, including fully schematic constructions (opened, in which the slots can be filled by any elements, such as: support verb + NP) to those that are closed constructions (with a substantive nature, without the possibility of slots to fill, as in: Deixar a peteca cair), going through semi-opened constructions (with a partialy schematic nature, in which just a few slots can be fill lexically, as in: deixou uma imagem ruim). These configurations indicate, according to Vieira (2014), the existence of three types of VN constructions: (i) non-lexicalized; (ii) semi-lexicalized; (iii) lexicalized. Therefore, we will analyze the occurrences of these constructions collected in the Corpus do Portugues (DAVIES and FERREIRA, 2006), considering productivity, in terms of frequency (BYBEE, 2003; 2010), and the compositionality. Thus, we can verify the hypothesis that these constructions are outputs of two distinct process of constructionalization grammatical and lexical constructionalization.
Keywords: Constructional approach; Verbal-noun constructions; Schematicity